Balance Board Sensory to Increase Body Balance’s Children with Special Needs - M. Haris Satria; Selvi Atesya Kesumawati; Desi Arisandy; Mutiara Karama (UNIB Press, 2023)
Children with special needs is a child who has obstacles in his growth and development. Children with special needs with multiple disabilities are children who have special learning needs and barriers caused by a combination of barriers and special learning needs caused by a combination of physical, sensory, social, emotional, intellectual and others. The condition of this multiple obstacle varies greatly depending on the type of mild and severity of the obstacle experienced. This study aims to produce an educational game tool (APE) to assist teachers and parents coaches in stimulating motor skills related to static and dynamic balance’s children with special needs. The research methods model used is ADDIE (Analysis, Design, Development, Implementation, and Evaluation), involving 4 teachers and 20 students with special needs (8-12 years olds). expert judgment in this study consisted of 4 experts, consisting 2 learning media experts, 1 psychologist, and 1 adaptive physical educator. Expert analysis of APE balance board sensory product using CVI and CVR, based on the result of the analysis, an average score of 0.7 which means the validity is high and it can be concluded that APE balance board sensory help teachers and parents stimulate the static and dynamic balance skill children with special needs.